The Input Analysis of Filling The Preeclampsia Screening Sheet in The Maternal and Child Health Handbooks in Tegal Regency - Ustriyaningsih Ustriyaningsih; Martha Irene Kartasurya; Ayun Sriatmi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
In 2019-2021, Preeclampsia has been among the highest causes of maternal death in the Tegal Regency. Early detection of preeclampsia risk factors is done by filling out the screening sheet in the Maternal and Child Health (MCH) Handbooks. However, its implementation has not been carried out properly. This study aims to analyzes the input factors the filling out of preeclampsia screening sheets by doctors in Tegal regency. The research was conducted qualitatively with phenomenological approach. This research started from October to December 2022. There were 2 main informant from the Head of the Division and Sub-Coordinators at the Health Office and 12 triangulation informant there where the Head of the Health Center, Coordinating doctors and midwives. Data collection techniques are conducted by in-depth interviews. Analysis of the research data is data reduction, data presentation and drawing conclusions. The results of the screening sheets were completely filled out showed 12.5%. The limited human resource is overcome by collaboration between health workers. Doctors' willingness to fill out screening sheets is still lacking. The infrastructure form of physical and laboratory examination tools is available and sufficient; the shortage of preeclampsia screening sheets is fulfilled by duplicating these sheets. Guidelines in the preparation stage, implementation of filling out the preeclampsia screening sheet, it was mostly done by midwives, and there was still non-compliance in filling out the management of screening results. Indeed, filling out the preeclampsia screening sheet had not gone well, and mostly done by midwives. It is recommended that the Health Service make a circular and guidelines for filling out the preeclampsia screening sheet. The head of the Community Health Center prepares a daily schedule, clarifies the duties and authority of doctors and midwives, and creates a service flow.Keyword: Input factor, Maternal and Child Health Handbook, Preeclampsia screening sheet